Struggling for Islamic Caliphate in a Changing Malay Society - Zulkifli, Zulkifli (Ulumuna, 2024)
Despite being banned by the government, HTI continues to struggle for Islamic caliphate as a clandestine movement. This study is aimed to explain factors resulting in the relatively successful penetration of caliphate ideology in a changing Malay society, as represented by Bangka Belitung Archipelagic Province. It employed a qualitative approach through the library study of both offline and online data sources in order to gain a holistic comprehension of HTI’s success. The research results elaborate HTI’s mobilization strategies as the internal factor and the context of changing Malay society and the dysfunction of moderate socio-religious organizations as the external factor contribute to HTI’s success in the changing society. Mobilization strategies comprising the intensive implementation of religious learning and preaching, publication, public demonstration, good relation and network with local important figures, and the competent use of communication and information technology become effective in the context of changing Malay society reconstructing identity and seeking solutions to its social and economic problems. In addition, the dysfunction of moderate socio-religious organizations producing a theological vacuum accentuates HTI’s relative victory. Thus, the performance of HTI depends on its internal capabilities and external context and the function of socio-religious organizations in society.